MODERN GRAPHIC DESIGN: SPECIFICS OF THE INTEGRAL NATURE OF CREATIVITY - Гула, Є. П. (Art and Design, 2020)
Purpose. To study the features and peculiarities of defining the main definitions of the concept of graphic design, to define the scope of application of various types of graphic art as a design object. Methodology. General scientific research methods, analytical, typological, semantic and comparative analysis – for the terminological definition of the conceptual apparatus of graphic design and the definition of its theoretical and art applications. Results. Based on the analysis of scientific sources on modern foreign and Ukrainian graphic design, generalized aspects of interpretation of the concept of graphic design, evaluated its historical origins in Ukraine. The issue of differentiation of graphic design and many areas of graphic design as a type of artistic activity has been updated. The scientific novelty consists in identifying trends in the transition of the terminological apparatus of industrial design to the sphere of graphic design. It has been established that the synthetic creative nature of graphic design provides for creative activity on the use of modern means of information transfer in combination with the traditions of graphic art of Ukraine. Practical significance. Modern scientific definitions of graphic design have been summarised. It has been determined that the synthetic creative nature of graphic design provides for creative activity on the use of modern means of infrmation transmission in combination with the traditions of graphic art of Ukraine. The results can be used in teaching graphic design, project graphics and other graphic disciplines.